Meter Placement for Distribution System State Estimation: An Ordinal Optimization Approach - Singh,R; Pal,BC; Jabr,RA; Vinter,RB (IEEE Transactions on Power Systems, 2011)
This paper addresses the problem of meter placement for distribution system state estimation (DSSE). The approach taken is to seek a set of meter locations that minimizes the probability that the peak value of the relative errors in voltage magnitudes and angle estimates across the network exceeds a specified threshold. The proposed technique is based on ordinal optimization and employs exact calculations of the probabilities involved, rather than estimates of these probabilities as used in our earlier work. The use of ordinal optimization leads to a decrease in computational effort without compromising the quality of the solution. The benefits of the approach in terms of reduced estimation errors is illustrated by simulations involving a 95-bus UKGDS distribution network model.